Imprisoned words – on language in aphasia - Panasiuk, Jolanta (Język(i) w czasie i przestrzeni, 2021)
Behavioral disorders stemming from the brain injury have long been treated as a natural experiment, owing to which the facts, normally highly complicated, appear in an elementary, broken-down form. The field of experiments in the studies on linguistic behaviors is thus descriptions of aphasic disorders. The repertory of problems that are part of these studies is very broad, the more so that the development of clinical procedures, the increasingly frequent attempts to develop a theory that would explain language disorders occurring in aphasic patients as well as the need for the treatment of aphasic speech disorders caused representatives of different disciplines, including linguistics, to be keenly interested in this problem. The article presents the main directions of interdisciplinary studies on aphasia, the evolution of the views on the brain-mind-language relationship, as well as the changes that have taken place in interpreting the phenomenon of aphasia and in assessing the linguistic abilities of aphasic persons.